A scheme to improve the international inter-library loan service in the National Library of China. Issue 2 (12th August 2014) - Feng, Jing'an
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a scheme to promote and improve international interlibrary loan (ILL) service at the National Library of China (NLC). The NLC is the center for international ILL in all of China, but as user needs change in response to the rapid development of information technology, it is necessary to investigate how to recast the international ILL service of the NLC. Design/methodology/approach – The paper uses a systematic case study approach. First, a brief introduction to international ILL practice in the NLC is given. Second, issues that concern request communications, copyright and payment methods are analyzed. Next, a scheme to modernize and improve international ILL is proposed as a response to the aforementioned problems. Finally, new challenges to international ILL are analyzed. Findings – The NLC should make the following efforts to improve international ILL service: enhance and expand the number of request transmission methods, update the legacy ILL and document delivery system, create a Chinese interlibrary loan alliance and fashion more reasonable copyright and payment policies. In addition, it should foster sustained innovation to meet the ongoing challenges to international ILL in the information age. Originality/value – This paper offers practical solutions for Chinese libraries engaged in international ILL activities.